2018
DOI: 10.1016/j.isci.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Fitness Profiling of Zika Virus E Protein Reveals Different Roles for Glycosylation during Infection of Mammalian and Mosquito Cells

Abstract: SummaryZika virus (ZIKV) infection causes Guillain-Barré syndrome and severe birth defects. ZIKV envelope (E) protein is the major viral protein involved in cell receptor binding and entry and is therefore considered one of the major determinants in ZIKV pathogenesis. Here we report a gene-wide mapping of functional residues of ZIKV E protein using a mutant library, with changes covering every nucleotide position. By comparing the replication fitness of every viral mutant between mosquito and human cells, we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
2
27
2
Order By: Relevance
“…Similar results have been also found in both WNV and tick-borne encephalitis virus (TBEV) (59,66). Moreover, this glycosylation is critical for ZIKV infection of mammalian and mosquito hosts (71,72) and antagonizing to the vector immune defense (73). In the present study, we demonstrate that nonglycosylation on the E protein of TMUVs results in limited virus replication (not systemic infection in ducks) and abrogation of virus transmission.…”
Section: Figsupporting
confidence: 87%
“…Similar results have been also found in both WNV and tick-borne encephalitis virus (TBEV) (59,66). Moreover, this glycosylation is critical for ZIKV infection of mammalian and mosquito hosts (71,72) and antagonizing to the vector immune defense (73). In the present study, we demonstrate that nonglycosylation on the E protein of TMUVs results in limited virus replication (not systemic infection in ducks) and abrogation of virus transmission.…”
Section: Figsupporting
confidence: 87%
“…By using this plasmid and also choosing a viral strain (MR766) that grows to high titer in cell culture, we were able to generate viral libraries that effectively sampled all amino-acid mutations to E protein. This library diversity contrasts to two other recent ZIKV deep mutational scanning studies 21,22 : both of these studies revealed important biological insights about host adaptation, but neither produced a complete map of amino-acid level selection due to an inability to generate and maintain the viral library diversity to sample all amino acids. Of course, our experiments were still subject to noise, probably because even our high-efficiency reversegenetics had some bottlenecking of viral diversity.…”
Section: Discussioncontrasting
confidence: 76%
“…To validate the antibody-escape mutants, we chose two mutations expected to strongly affect sensitivity to each anti-ZIKV antibody (A333T and T335E for ZKA64, and D67A and K118R for ZKA185). We performed neutralization assays against viruses engineered to contain these mutations, using a previously described approach 14,22,32 . As expected from the mutational antigenic profiling, each mutation greatly reduced neutralization sensitivity to the antibody that selected it, but not to the other antibody (Fig 5E,F,G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations